Intra-EU vs. extra-EU trade in ICT services - Joanna Stefaniak; Adam A. Ambroziak (International Journal of Management and Economics, 2021)
The position of information and communication technology (ICT) services is growing in the European Union (EU) trade, however to different extend in different EU countries. The article aims to identify trade positions of the EU Member States in intra-EU trade and extra-EU trade in ICT services and to assess changes that have taken place in the years 2013-2018. The importance of the EU Member States in trade in ICT services is assessed, followed by the analysis of their trade positions in terms of selected indices. We discovered that countries of the highest importance for the intra-EU and extra-EU trade in ICT services are not holding the best positions in trade in this area, except for Ireland. Additionally, leaders in ICT services trade do better in extra-EU trade rankings than in the EU Internal Market, since the distance does not matter to business operations consequent to the digitalization of economic activities.
Keywords: F15; F55; O52; 650; ICT services; extra-EU trade; intra-EU trade; services trade; RSCA